Evaluation of Short-Term Insulin Pump for Treatment of Patients with Type 2 Diabetes Mellitus Complicated with Lower Extremity Arterial Disease in Endocrinology by Ultrasonography. (27th May 2022) - Guo, Qiongyao; Li, Zhouyue; Chen, Hua
Abstract : This research aimed to explore the curative effect of short-term insulin pump in the treatment of type 2 diabetes mellitus (T2DM) patients with lower extremity arterial disease (LEAD) based on ultrasonography. 422 patients (220 males and 202 females) with T2DM in the hospital were selected, and they were randomly divided into control group (n = 211, oral hypoglycemic drugs or diet control, appropriate exercise to lower blood glucose) and experimental group (n = 211, insulin pump was used to reduce blood glucose). After 2 weeks, the therapeutic effect was evaluated by ultrasonography. The results showed that after two weeks of treatment, the difference in lumen intima between the two groups was statistically significant (P < 0.05 ). The intima-media thickness (IMT) values of the experimental group were 0.83 ± 0.03   mm, 0.62 ± 0.03   mm, and 0.41 ± 0.04   mm, respectively, which were significantly different from those of the control group (1.62 ± 0.54   mm, 1.23 ± 0.14   mm, and 0.78 ± 0.11   mm ) (P < 0.05 ). There was obvious difference in low-density lipoprotein cholesterol (LDL-C) level between the experimental group (2.22 ± 0.46   mmol / L ) and the control group (3.21 ± 0.62   mmol / L ) (P < 0.05 ). The LEAD score of the experimental group was 5.51 ± 1.11, which was significantly different from that of the control group (7.08 ± 2.73 ) (P < 0.05 ). There was clear difference in LEAD score between the two groups under different course of disease (CD) (P < 0.05 ). Studies indicated that short-term application of insulin pump therapy could effectively improve the pathological changes of lower limbs in patients with T2DM, which had clinical application value.